Keterampilan Abad 21 Siswa SMK di Era Digital: Analisis Implementasi KOSP di SMKN 1 Sukabumi - Supriatno, Empri; Rachmawati, Ike (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the digital era, vocational students require 21st-century skills to face challenges and opportunities brought forth by the independent curriculum and Industrial Revolution 4.0. This study evaluated the readiness and effectiveness of SMKN 1 Sukabumi City's Education Unit Operational Curriculum (KOSP) in developing these skills. Using literature study and data analysis techniques, the study found that while the KOSP has great potential, improvements are necessary. Attention should be given to integrating 21st-century skills in all subjects, developing innovative and collaborative learning models, and improving learning facilities and resources. While effective, further development and periodic evaluation of the KOSP, as well as teacher and student training, are recommended for continued success in preparing vocational students for the digital era.